The World of Friendship Forest - Björk, Pasi; Halonen, Jorma (Open Schools Journal for Open Science, 2019)
The World of Friendship Forest project is located in the Finnish town of Salo, where the School of Uskela, Anjalankatu Unit has implemented various smaller projects in their nearby forest to engage students in meaningful and interesting activities which provide benefit for the whole town community. The school provides special education for grades 1 to 9 (ages 7 to 16) and the European Project Open Schools for Open Societies ( OSOS) projects so far have involved 60 students in total. The students of the school have extensive learning difficulties and behavioural and emotional troubles. Most students have a low socioeconomic status. Majority of the students also have low self-esteem.  From the point of view of students’ overall development, it has been important to provide them with socially significant activities and to provide students with experiences of success and sense of togetherness. The main partners in the project have been the sports office of the town and schools of Tupuri and Uskela, Kavilankatu unit and the University of Turku.